2018
DOI: 10.1161/hypertensionaha.117.10713
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Blood Pressure Targets for Diabetic and Other High-Risk Populations

Abstract: Optimal blood pressure (BP) targets for different populations, especially diabetics, remain uncertain after conflicting data on intensive management. We assessed whether a <120 mm Hg systolic target is beneficial and whether certain patient populations differ in response. Individual patient data of 14 094 patients from 2 randomized control trials was pooled. Seven thousand forty patients were assigned to an intensive target of <120 mm Hg and 7054 patients to a standard target of <140 mm Hg in an intention-to-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…In addition, 33% of the ACCORD, and 17% of the SPRINT populations had a previous cardiovascular event, which leaves very few patients with normotension and coronary artery disease. Overall, even though the combined analysis of these trials favoured intensive treatment, 13 no clear conclusion can be drawn on intensive BP-lowering in normotensive patients with coronary artery disease. Noteworthy, in SPRINT, mean age was 7 years older than in CLARIFY, and patients with diabetes or previous stroke were excluded, also limiting the comparison between these two studies.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, 33% of the ACCORD, and 17% of the SPRINT populations had a previous cardiovascular event, which leaves very few patients with normotension and coronary artery disease. Overall, even though the combined analysis of these trials favoured intensive treatment, 13 no clear conclusion can be drawn on intensive BP-lowering in normotensive patients with coronary artery disease. Noteworthy, in SPRINT, mean age was 7 years older than in CLARIFY, and patients with diabetes or previous stroke were excluded, also limiting the comparison between these two studies.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, Rahul Aggarwal reported that the combination of T2DM and hypertension is more likely to be associated with person who is older, male, higher BMI and less physical activity [ 33 ], a reasonable diet, exercise, weight control, and central obesity control are useful in preventing hypertension [ 34 37 ]. Previous studies have also provided us with evidence of aggravation of organ damage caused by alcohol in diabetic patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causal relations need to be determined through randomized controlled trials, as observational study designs have inevitable drawbacks (eg confounding factors). As mentioned, some clinical trials have shown the benefit of lowering BP below 'normal' levels among strictly selected patients [3]. However, in general practice, patients with hypertension alongside comorbidities such as atherosclerosis, atrial fibrillation, and heart failure are sometimes unintentionally treated to low BP levels, Therefore, the objective of the current study is to provide reliable information on the relationship between baseline BP levels and long-term mortality from CVD in a large sample and use differential analysis to examine whether the association varied by antihypertensive medication use.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that high blood pressure (BP) increases the risk of cardiovascular disease (CVD) [1], and that treatment of hypertension reduces that risk [2]. Clinical trials have shown that treating hypertension to below-normal BP levels is better for the prevention of coronary heart disease or stroke among patients with high cardiovascular risk [3]. On the other hand, several prospective cohort studies have shown that among patients treated for hypertension treatment to low BP levels was associated with increased risk of coronary heart disease and/or stroke compared with treatment to moderate BP levels [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation